Lessons from Hippocrates for contemporary urban health challenges. Issue 1 (2nd January 2017) - Lawrence, Roderick; Capon, Anthony; Siri, José
Abstract: Complexity is the hallmark of our habitats, our livelihoods and our health. These objects of analysis, understanding and intervention extend from our homes to our streets and neighbourhoods, to the cities and regions beyond our immediate surroundings. They are inscribed in ecological and geopolitical systems that span international and planetary levels. Over two millennia ago in Classical Greece, Hippocrates wrote about the complex web of interconnections that influence health and well-being. To achieve desired outcomes in the cities of today and tomorrow, we must transcend purely biomedical models and apply the principles of ecological public health. Collaborative systems thinking involving different disciplines and professions is essential for the implementation of this new approach, which adopts an integrated conceptual framework drawn from human ecology. This framework can underpin a shared understanding of the interdisciplinary concepts that must be applied during the transdisciplinary processes needed to address urban health challenges. This new approach is particularly important for the implementation of the United Nations' 2030 Agenda for Sustainable Development, the New Urban Agenda and related global agreements, as we strive for effective promotion of urban health and well-being in a rapidly changing world.